2004
DOI: 10.1182/blood.v104.11.1439.1439
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation and Immunosuppressive Therapy in Children with Aplastic Anemia: Data from a Prospective Multinational Trial in Germany, Austria and Switzerland.

Abstract: In children severe aplastic anemia is a rare, lifethreatening disease. Patients present with peripheral pancytopenia and hypoplastic bone marrow. The disease is sub-classified into a severe (PMNs >200/μl: SAA) and a very severe (PMNs <200/μl: vSAA) form. Children with vSAA are especially prone to die from infectious complications. Bone marrow transplantation (BMT) and immunosuppressive therapy (IST) are the two treatment options. However, most of the affected children lack a compatible sibling donor (MSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Führer et al 22 reported five publications including one original article, a follow-up article, 23 one protocol 24 and two abstracts. 25 26 We did not identify any RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Führer et al 22 reported five publications including one original article, a follow-up article, 23 one protocol 24 and two abstracts. 25 26 We did not identify any RCTs.…”
Section: Resultsmentioning
confidence: 99%